Evaluasi Implementasi Fatwa DSN-MUI Nomor 123 Tahun 2018 terkait Dana TBDSP pada Lembaga Keuangan Syariah sebagai Pedoman Optimalisasi Penyaluran Dana Kebajikan - Ardiansyah Ashri Husein; Oyo Sunaryo Mukhlas (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
DSN-MUI Fatwa Number 123/DSN-MUI/XI/2018 provides essential guidelines regarding the use of Funds Not Recognized as Income (TBDSP) within Sharia Financial Institutions (LKS). This fatwa was issued in response to operational practices that generate funds from non-Sharia transactions, such as correspondent bank interest and late payment penalties (ta'widh and gharamah). This study aims to analyze the implementation of the fatwa in Indonesia to optimize the distribution of benevolent funds (dana kebajikan). It employs a normative-juridical method utilizing statutory, conceptual, and fatwa-based approaches. The findings indicate that most Sharia banks have implemented the segregation of TBDSP funds from operational income for distribution toward social activities. However, implementation faces challenges regarding inconsistent accounting standards, reporting transparency, and Sharia oversight. As a novel contribution, this study asserts that optimizing TBDSP funds as benevolent funds has significant implications for educational transformation. If strategically allocated to the education sector, these funds can serve as a pillar of alternative financing to enhance academic infrastructure and the quality of human resources. Therefore, it is necessary to strengthen regulations, enhance the role of the Sharia Supervisory Board (DPS), and harmonize rules to ensure that fund distribution adheres to the principles of maqāṣid al-syarī‘ah, transparency, and accountability.